Skin Immunity and Tolerance: Focus on Epidermal Keratinocytes Expressing HLA-G - Mestrallet, Guillaume; Rouas-Freiss, Nathalie; LeMaoult, Joel; Fortunel, Nicolas O.; Martin, Michele T. (Frontiers in Immunology, 2021)
Although the role of epidermal cells in skin regeneration has been extensively documented, their functions in immunity and tolerance mechanisms are largely underestimated. The aim of the present review was to outline the state of knowledge on resident immune cells of hematopoietic origin hosted in the epidermis, and then to focus on the involvement of keratinocytes in the complex skin immune networks acting in homeostasis and regeneration conditions. Based on this knowledge, the mechanisms of immune tolerance are reviewed. In particular, strategies based on immunosuppression mediated by HLA-G are highlighted, as recent advances in this field open up perspectives in epidermis-substitute bioengineering for temporary and permanent skin replacement strategies.